Gut Resistome After Oral Antibiotics in Preschool Children in Burkina Faso: A Randomized, Controlled Trial. (31st May 2019) - Oldenburg, Catherine E; Hinterwirth, Armin; Sié, Ali; Coulibaly, Boubacar; Ouermi, Lucienne; Dah, Clarisse; Tapsoba, Charlemagne; Cummings, Susie L; Zhong, Lina; Chen, Cindi; Sarkar, Samarpita; Bärnighausen, Till; et al.
Abstract: We evaluated the effect of systemic antibiotics (azithromycin, amoxicillin, cotrimoxazole, or placebo) on the gut resistome in children aged 6 to 59 months. Azithromycin and cotrimoxazole led to an increase in macrolide and sulfonamide resistance determinants. Resistome expansion can be induced with a single course of antibiotics.